Impact of the COVID-19 pandemic on CHD care and emotional wellbeing - Cousino, Melissa K.; Pasquali, Sara K.; Romano, Jennifer C.; Norris, Mark D.; Yu, Sunkyung; Reichle, Garrett; Lowery, Ray; Viers, Suzanne; Schumacher, Kurt R. (Cardiology in the young, 2021)
Understanding the impact of the COVID-19 pandemic on paediatric non-COVID-19-related care, as well as patient and caregiver concerns and stressors, is critical for informing healthcare delivery. It was hypothesised that high care disruptions and psychological stress would be observed among paediatric and adult CHD patients in the early phase of the pandemic. A cross-sectional, international, electronic survey study was completed. Eligible participants included parents of children with acquired or CHD, adults with CHD, or caregivers of adults with CHD. A total of 1220 participants from 25 countries completed the survey from 16 April to 4 May, 2020. Cardiac care disruption was significant with 38% reporting delays in pre-pandemic scheduled cardiac surgeries and 46% experiencing postponed cardiac clinic visits. The majority of respondents (75%) endorsed moderate to high concern about the patient with heart disease becoming ill from COVID-19. Worry about returning for in-person care was significantly greater than worry of harm to patient due to postponed care. Clinically significant psychological stress was high across the sample including children (50%), adults with CHD (42%), and caregivers (42%). The early phase of the COVID-19 pandemic contributed to considerable disruptions in cardiac care for patients with paediatric and adult CHD. COVID-19-related fears are notable with potential to impact willingness to return to in-person care. Psychological stress is also very high necessitating intervention. Further study of the impact of delays in care on clinical outcomes is warranted.